Factors Affecting Prairie Settlement: A Case Study of Abernethy, Saskatchewan, in the 1880s - Dick, Lyle (Historical Papers / Communications historiques, 1985)
AbstractPrairie agricultural settlement in the era of the National Policy has often been viewed as an organic process which rewarded the resourceful settlers, while punishing the unsuitable ones. To test this assumption the paper offers a detailed investigation of settlement in two districts in Saskatchewan. The three areas of analysis were the process of land acquisition, the settlers' performance during the homestead "proving- up" period, and long-term economic performance after the receipt of patent.In terms of land acquisition, both Anglo-Canadian settlers in the Abernethy district and German-speaking settlers at Neudorf chose the available lands nearest the railway. Their selection suggests an initial tendency toward commercial production among both groups. The difference was that Abernethy settlers, who generally arrived in the 1880s, claimed superior lands on the open prairie. While about half of these settlers never "proved-up" their homesteads, those who received their patents showed a fairly high degree of persistence as farmers. A close relationship between the receipt of additional quarter-sections of free grant land and long-term economic success was also observed.The German settlers at nearby Neudorf, who settled in the ¡890s on more marshy and wooded lands, showed a contrary tendency. These settlers were far less likely to cancel their homestead entries, but tended to leave their farms soon after receiving their patents. Studies of the long-term economic performance of settlers in both dis- tricts provide support for the proposition that early arrival, and the acquisition of good, cheap, accessible land were among the most powerful determinants of success in settlement.